2014
DOI: 10.1021/tx500291t
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Metabolites of the Fungicide Tebuconazole in Human Urine

Abstract: Tebuconazole (TEB) is a fungicide used in agriculture; the objective of this work was to identify and quantify TEB metabolites in human urine. Samples from seven vineyard workers exposed to TEB were submitted to liquid chromatography interfaced with a triple quadrupole mass spectrometer, equipped with an electron spray source, and a linear ion trap to gain a profile of candidate metabolites. Based on the presence of the ion m/z 70 in the MS/MS spectra, which corresponds to protonated triazole (a specific moiet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 10 publications
4
22
0
2
Order By: Relevance
“…52 In human urine, hydroxyl and carboxyl products of tebuconazole were identified as major BTPs, both free and as glucuronide conjugates. 60 For propiconazole, the large majority of BTPs identified in mammals contained the unchanged triazole ring which is in line with our results. 52 Little data is available for epoxiconazole.…”
Section: Comparison With Literature Data For Other Speciessupporting
confidence: 92%
“…52 In human urine, hydroxyl and carboxyl products of tebuconazole were identified as major BTPs, both free and as glucuronide conjugates. 60 For propiconazole, the large majority of BTPs identified in mammals contained the unchanged triazole ring which is in line with our results. 52 Little data is available for epoxiconazole.…”
Section: Comparison With Literature Data For Other Speciessupporting
confidence: 92%
“…As a triazole fungicide, TEB has been widely used in agriculture, leading to adverse effects on humans and wildlife (Sivikova, Dianovsky, Holeckova, Galdikova, & Kolesarova, ; Renzo et al, 2011; Castro et al, ; Bernardes, Andrade‐Vieira, Aragao, Ferreira, & Ferreira, ; Mercadante et al, ). The persistence in the environment and long half‐life mean that transgenerational investigation by parental exposure becomes very significant.…”
Section: Discussionmentioning
confidence: 99%
“…A survey conducted by Lefrancq et al assessed 20 runoff events from 2009 to 2012 at the outlet of a vineyard catchment in the Layon catchment in France and the results showed that the concentration of TEB could reach 357 μg/L (Lefrancq, Jadas‐Hecart, La Jeunesse, Landry, & Payraudeau, ). Evidence showed that the metabolites of TEB in agricultural workers ranged from 3 to 473 μg/L in urine (Mercadante, Polledri, Scurati, Moretto, & Fustinoni, ). Additionally, an increase in TEB levels in agricultural workers ranging from 15.5 to141.3 pg/mg hairs, which indicated that TEB could accumulate in hair during the agricultural season (Mercadante, Polledri, Moretto, & Fustinoni, ).…”
Section: Introductionmentioning
confidence: 99%
“…7 The aim of this work was to identify the major metabolites of PEN in human urine; this was achieved analyzing samples of agricultural workers exposed to PEN by LC-QqLIT MS; the second aim was to estimate the abundance of these metabolites to orientate the choice of a molecular marker for biomonitoring human exposure.…”
Section: ■ Introductionmentioning
confidence: 99%